2021
DOI: 10.1186/s13054-021-03840-x
|View full text |Cite
|
Sign up to set email alerts
|

Real-world corticosteroid use in severe pneumonia: a propensity-score-matched study

Abstract: Background Community-acquired pneumonia (CAP) is a leading cause of morbidity and mortality worldwide despite correct antibiotic use. Corticosteroids have long been evaluated as a treatment option, but heterogeneous effects on survival have precluded their widespread implementation. We aimed to evaluate whether corticosteroids might improve clinical outcomes in patients with severe CAP and high inflammatory responses. Study design and methods We an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…SP is one of the clinical high incidence diseases, which is mostly caused by Inflammatory reaction caused by pulmonary infection is considered one of the major causes of SP and SP-associated high mortality. 13 The inflammatory response in patients with SP leads to the injury of pulmonary vascular endothelial cells, the increase of the expression of fibrinolytic inhibitory factors and procoagulant factors, resulting in the activation of the coagulation system, the occurrence of hypercoagulability and local micro thrombosis. The increase in fiber composition of lung tissue, and the occurrence of hypoxemia, hypoxemia and uncontrolled lung inflammation can lead to lung tissue injury, and in severe cases, to life threatening septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…SP is one of the clinical high incidence diseases, which is mostly caused by Inflammatory reaction caused by pulmonary infection is considered one of the major causes of SP and SP-associated high mortality. 13 The inflammatory response in patients with SP leads to the injury of pulmonary vascular endothelial cells, the increase of the expression of fibrinolytic inhibitory factors and procoagulant factors, resulting in the activation of the coagulation system, the occurrence of hypercoagulability and local micro thrombosis. The increase in fiber composition of lung tissue, and the occurrence of hypoxemia, hypoxemia and uncontrolled lung inflammation can lead to lung tissue injury, and in severe cases, to life threatening septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, concerns about the reproducibility of these results have limited applicability thereof [79]. Recently, in a propensity score matching study using real-life data [102], our group observed significantly lower mortality in those patients with severe CAP criteria per ATS/IDSA guidelines [79]. Corticosteroids also reduced the risk of disease progression to ARDS [97].…”
Section: Managing Ards Due To or Complicated By Respiratory Infectionsmentioning
confidence: 98%
“…A recent multicentre study from Spain and Italy [ 67 ] compared patients with sCAP who did and did not receive corticosteroids. Investigators excluded patients receiving hydrocortisone and/or with a CRP level of <15 mg·dL −1 in the blood.…”
Section: Use Of Corticosteroids As Adjunctive Therapy In Scapmentioning
confidence: 99%